Comparative study on ultra-low-cycle-fatigue behavior of Q235 normal-steel and Q690 high-strength steel. (July 2022) - Huang, Xuewei; Yuan, Yilin; Zhao, Jun; Wei, Chenchen
Abstract: In this study, monotonic tensile and ultra-low-cycle-fatigue tests were conducted on Q235 normal steel and Q690 high-strength steel to investigate their fracture behavior under various stress states. The experimental results indicate that the deformability of Q690 steel under monotonic loading and its fatigue life under ultra-low cyclic loading were significantly lower than those of Q235 steel. Moreover, the ductility and fatigue resistance of Q690 steel were also much lower, in particular, under plane strain condition. However, the difference in energy dissipation capacity between the two types of steels was small due to the higher strength of Q690 steel. A continuous damage mechanics (LCDM) model used under monotonic loading was extended to the case of ultra-low-cycle-fatigue loading; however, the experimental results reveal that the LCDM model overestimated the damage accumulation rate of the two steels. Based on the concept of different dislocation structure movements, a new continuous damage mechanics model named as CLCDM was proposed to predict ultra-low-cycle-fatigue failure. In this model, the damage was divided into isotropic hardening part and kinematic hardening part, and the relationship between the two parts was described by a parameter considering the influence of cyclic loading. The CLCDM model was applied to investigate ultra-low-cycle-fatigue behavior of a connection tensile specimen with initial gap. The results demonstrate that the fracture process and fatigue life of the specimen obtained by numerical simulation are in good agreement with experimental observations, and the prediction accuracy of the CLCDM model is significantly higher than that of the LCDM model. Highlights: Monotonic and ULCF tests were conducted for Q235 normal steel and Q690 high strength steel. ULCF fracture behavior of Q235 steel and Q690 steel under various stress states was compared. The ULCF damage was divided into isotropic hardening part and kinematic hardening part. A new continuous damage mechanics model was proposed to predict ULCF failure of steels. The CLCDM reveals higher accuracy than the LCDM in predicting ULCF of the joint specimen.